The poverty impacts of the Doha Round in Cameroon : the role of tax policy - Emini, Christian Arnault (Policy research working paper, 2005)
"The authors aim to assess the possible impacts of the Doha Round of negotiations on poverty in Cameroon. During the recent period of economic recovery, Cameroon enjoyed a sharp decline in poverty, with the headcount index falling from 53.3 percent of inhabitants in 1996 to 40.2 percent in 2001, mostly due to economic growth rather than redistribution. Will the current trade negotiations under the Doha Round reinforce or curb this trend? They apply a computable general equilibrium (CGE) microsimulation model that involves 10,992 households in order to address this question. The authors find the Doha Round to be poverty-reducing for Cameroon. For the whole country, the estimate of the net number of people who are lifted out of poverty is 22,000 following this scenario. Further investigations indicate that more ambitious world trade liberalization leads to greater poverty alleviation at the national level, while Cameroon's domestic trade liberalization has adverse poverty and inequality impacts-despite giving rise to higher aggregate welfare. Under the Doha scenario, the cuts in Cameroon's tariffs are very small (the average tariff rate moves from 11.79 percent in the base run to merely 11.66 percent) so that world trade liberalization effects on prices more than offset the adverse own liberalization effects in this scenario. If the rest of the world and Cameroon full trade liberalizations are combined, the adverse impacts of own liberalization outweigh the favorable outcomes of the world trade liberalization. The results suggest furthermore that the choice of tax replacement instrument can have an important bias in poverty impacts: poverty gets worse in the country case study when using an imperfect value-added tax instead of a neutral replacement tax to compensate lost tariff revenue, and gets even worse when using a consumption tax.